Pengaruh Model Mobilitas Node Pada Protokol Routing AODV dalam MANET - Laisa Ryry Pudja Mentari; Rakhmadhany Primananda; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Ad-Hoc Network (MANET) is one type of Ad-hoc Network that consist of independent wireless nodes. Each node can act as a relay and transmit a message to the other nodes that indirectly connected. In MANET, the nodes are moving dynamically so that it allows the use of different types of mobility model. However, the use of mobility models can lead into higher possibility of diconnection and higher routing failure. It could impact on the quality of network performance and became one of the important factor to considered when measuring the quality of network performance. There are some routing protocols that are used on MANET, one of which is Ad-Hoc on Demand Distance Vector (AODV). AODV is used because it is one of the most rapid adaptive routing protocols for dynamic link conditions. This research provided an analysis of the effect of node mobility on AODV in MANET topology using Network Simulator 3.25. Research was conducted using Random Waypoint (RWP) and Random Direction (RD) mobility model by measuring network performance metrics specifically packet delivery ratio (PDR), average end-to-end delay, and routing convergence time. Tests were conducted on both mobility models with scenario of 15, 25, 40, and 50 nodes variation and 750 m2 and 1250 m2 of simulation area. Measurement results show the highest PDR value is in RD with 92.27% in 750 m2 area. Meanwhile, the lowest end-to-end delay value is in RD with 25.93 ms in the ​​750 m2 area and the lowest routing convergence time value is in RD with 0.534 second on 750 m2 simulation area as well.